Medellín's Biblioteca España: Progress in Unlikely Places. Issue 1 (21st January 2014) - Holmes, Jennifer S.; Gutiérrez de Piñeres, Sheila Amin
The Biblioteca España, designed by Giancarlo Mazzanti, is a library park built to serve two traditionally marginalized comunas (neighborhoods) of Medellín. As such, it is a prime example of a public policy intervention that focuses on social inclusion, the provision of services, and quality of life. In this paper, we ask whether improvements in state capacity and infrastructure at the local level can have a broad impact in poor and violent communities. The survey results reveal that citizens of comunas Popular and Santa Cruz perceive their situation to be improving at a faster rate than those of the city in general. The broader lesson for other countries and cities facing similar challenges is that leadership and reforms do have the potential to improve the quality of life, even in the most troubled areas.